The Relevance of Muhammad Abduh's Thought in Indonesian Tafsir: Analysis of Tafsir Al-Azhar - Zulfikri Zulkarnaini; Mohammed A.F. Badawi (Millah: Journal of Religious Studies, 2021)
In this study, the author uses the descriptive-historical approach to explain the influence of Muhammad Abduh's thoughts and Tafsir Al-Manar's coming to Indonesia. Especially in the Tafsir Al-Azhar by Hamka, who was born in the 20th century. This interpretation emerged when Indonesia was experiencing a state of transition from colonialism to independence. At the same time, modern Islamic thought became strong in Indonesia. The modern approach of Tafsir al-Manar has inspired Hamka's model of interpretation in Tafsir Al-Azhar. Here the authors find similarities in terms of methodology, namely social-community (Adab ijtima'i). Apart from that, there are some similarities and differences between the Tafsir Al-Manar with Tafsir Al-Azhar. For example, the view of the verses of "Ahl Kitab, muhkam-mutasyabih, and Israiliyat." Then the implications for the understanding of the heterogeneous Indonesian Islamic community from various religions. Besides this, the interpretation had a significant influence on the development of modern interpretation in Indonesia. It is easy to read and understand the general public to academics in Indonesia, Malaysia, and other Southeast Asian countries.